Romania: National Identity and EU’s Common Values. Vision, Reality, Expectation - Cîrmaciu, Diana (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
Concepts such as financial policy and finance have always been emotionally charged. Some people are fascinated and guided by this field; others are frightened by the possible foreboding of dark days. Some hold notions that burden these concepts with all the sins that have arisen since the ‘creation of the world’ to the present day; others attribute to them the qualities of a universal panacea for all the problems of mankind. Examining these attitudes indicates that no one treats the issues of finance and financial policy with carelessness, despite their damaged behaviour. When the concept of finance is enriched by becoming public finance, interest is heightened. Each citizen, as a taxpayer or even if not a taxable person, forms their own perception of the concept of public finance and financial policy. In fact, the terms ‘budget’, ‘finance’, ‘austerity budget’, ‘rectification’, and ‘public debt’ are part of our everyday language, whether or not we are specialists in the field. Financial policies, and implicitly public finances, have always been seen as essential elements of the social and economic life of every nation; however, they are becoming increasingly prominent today. Public finances now occupy this important position because, in many countries of the world, a large part of the gross domestic product is channelled through financial instruments to central and local public authorities. Public finances exist to serve specific objectives and fulfil certain tasks that could not be achieved by any other means. They achieve their social mission through the distribution and control functions they perform. Though we cannot exhaust all sides of the complex issue of national financial policy and the relationship with European Union law in this chapter, we believe that solutions must combine orderly finances and well-thought-out policy that ensures a legal framework and human resources that understand and support general interests. Keywords: financial policy, public finance, state budget, strategies, financial balance